Strategi Pembelajaran Membaca dan Menulis Permulaan Melalui Media Kata Bergambar - Rahmawati Rahmawati (Universitas Indraprasta PGRI Jakarta, 2017)
The purpose of this research is to develop an Illustrated Word Medium (MKB) in a bid to improve the quality of early reading and writing activities in the 1st grade. Further, the specific purpose of this research is to test and to develop the prototypes of Illustrated Word Medium. The procedures for the development of this Illustrated Word Medium model are established based on the development steps of Research and Development (R & D) model. The data of the research are generated by using two types of instrument, namely interview and observation guidelines. This research then creates an Illustrated Word Medium product which has the characteristics and specifications that can be seen from (1) form, (2) size,(3) style of writing, (4) picture, (5) type ofthe words used and (6) color of Illustrated Word Medium.